Physiological and Biochemical Effects of Intermittent Warming on ’Marmandi’ Turning Tomato Fruits During Low-Temperature Storage - Abusasiyah, Mousa; Elmalki, Nadia; Abdurabbah, Salma (Journal of Pure & Applied Sciences, 2024)
This experiment was conducted on the variety 'Marmandi' turning tomato fruits to investigate the effect of intermittent warming temperatures during extended low chilling temperature storage (21 days) on the subsequent ripening quality of tomato fruits. The quality was measured by assessing the quantitative amount of total phenolic compounds, chlorogenic acid, and ascorbic acid, as well as the development of fruit color and the evaluation of chilling injury (CI) symptoms. The results indicated that the amounts of total phenolic compounds and chlorogenic acid increased significantly during continuous low-temperature storage and after subsequent transfer to room temperature, with this increase being associated with significant loss of ascorbic acid. More frequent periods of intermittent warming (IW) during low-temperature storage were very effective in significantly decreasing the rate of accumulation of phenolic compounds, chlorogenic acid, and ascorbic acid losses. A significant reciprocal relationship between the amounts of chlorogenic acid and ascorbic acid was observed. Additionally, the results showed that as IW time increased, its effectiveness in retarding CI significantly improved.